Characteristics of individuals with hemiparesis according to perception about the difficulty climb stairs - Cano, Fernando Wendelstein; Parizotto, Daniela; Michaelsen, Stella Maris (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: climbing up and down stairs is entered directly into the Community ambulation and activities of daily living. In individuals with hemiparesis after stroke, this activity may be compromised due to deficits in components of body function and structures, activity and participation. Objective: To identify the characteristics of individuals with hemiparesis, according to the self-perception of difficulty climbing stairs and relate to components of body function and structures (BFS), activity and participation with the cadence of up / down stairs. Method: Twenty-five subjects (57.8±12.4 years) with chronic hemiparesis (57.8±42.7 months) were divided into two groups as perceived with and without difficulty climbing stairs by this particular question in the Stroke Specific Quality of Life Scale (SSQOL). In the BSF domain was rated lower limb motor impairment (Fugl-Meyer Scale), the activity domain, gait/mobility (gait speed, the Timed Up and Go-TUG) and balance (one-leg support and BERG) and participation domain the quality of life with SSQOL. Results: The group with self-perception without difficulty showed less motor impairment and higher levels of activity and participation. Strong correlations of the stair climbing cadence with the Fugl-Meyer Scale and TUG and between stair descent cadence with gait speed and TUG. Conclusion: Variables of body function andstructures , activity and participation are lower in the group with self-perceived difficulty in stair climbing and are correlated with the cadence of stair ascent and descent.